Microbiological and Physicochemical Changes in Palm Wine Subjected to Spontaneous Fermentation During Storage - Afolabi, Folake Titilayo; Owoola, Akeem Temitope (The International Journal of Biotechnology, 2019)
This work aimed to isolate and identify yeasts obtained from palm wine subjected to spontaneous fermentation during storage. A total of forty (40) yeast isolates were from spontaneously fermented palm wine. The yeast counts obtained ranged from 5.46 x 104 cfu/ml at day one to 3.00 x 102 cfu/ml at day twenty-two. Saccharomyces cerevisiae was isolated at all stages of fermentation. The pH dropped from 3.70 at 24 hours to 3.37 at 360 hours. Total titratable acidity of the wine increased from 2.28% at 24 hours to 4.50% at 528 hours. Total sugar of the stored palm wine from decreased from 4.0211g/10 ml at 24 hours to 0.6417g/10 ml at 528 hours was observed. The reducing sugar content of the stored palm wine decreased from 13% at 24 hours to 0.960% at 456 hours was also observed. Ethanol content of the stored palm wine increased steadily from 21.06 mg/ml at 24 hours to 88.99mg/ml at 456 hours as the storage time increases. Palm wine whose storage time is not beyond 120 hours is not injurious to the health of consumers.